Brain Histopathology of Adult Decedents After Extracorporeal Membrane Oxygenation. (2nd March 2021) - Khan, Imad R.; Gu, Yang; George, Benjamin P.; Malone, Laura; Conway, Kyle S.; Francois, Fabienne; Donlon, Jack; Quazi, Nadim; Reddi, Ashwin; Ho, Cheng-Ying; Herr, Daniel L.; Johnson, Mahlon D.; et al.
Abstract : Objective: To test the hypothesis that brain injury is more common and varied in patients receiving extracorporeal membrane oxygenation (ECMO) than radiographically observed, we described neuropathology findings of ECMO decedents and associated clinical factors from 3 institutions. Methods: We conducted a retrospective multicenter observational study of brain autopsies from adult ECMO recipients. Pathology findings were examined for correlation with demographics, clinical data, ECMO characteristics, and outcomes. Results: Forty-three decedents (n = 13 female, median age 47 years) received autopsies after undergoing ECMO for acute respiratory distress syndrome (n = 14), cardiogenic shock (n = 14), and cardiac arrest (n = 15). Median duration of ECMO was 140 hours, most decedents (n = 40) received anticoagulants; 60% (n = 26) underwent venoarterial ECMO, and 40% (n = 17) underwent venovenous ECMO. Neuropathology was found in 35 decedents (81%), including microhemorrhages (37%), macrohemorrhages (35%), infarctions (47%), and hypoxic-ischemic brain injury (n = 17, 40%). Most pathology occurred in frontal neocortices (n = 43 occurrences), basal ganglia (n = 33), and cerebellum (n = 26). Decedents with hemorrhage were older (median age 57 vs 38 years, p = 0.01); those with hypoxic brain injury had higher Sequential Organ Failure Assessment scores (8.0 vs 2.0, p = 0.04); and those with infarction had lower peak PaCO2 (53 vs 61 mm Hg, p = 0.04). Six of 9 patients with normal neuroimaging results were found to have pathology on autopsy. The majority underwent withdrawal of life-sustaining therapy (n = 32, 74%), and 2 of 8 patients with normal brain autopsy underwent withdrawal of life-sustaining therapy for suspected neurologic injury. Conclusion: Neuropathological findings after ECMO are common, varied, and associated with various clinical factors. Further study on underlying mechanisms is warranted and may guide ECMO management.